A Case Report of Adenoviral Pneumonia with Splenic Infarction - Gajam Siddhartha; Preetham K Poddutoor; Sandhya Vaddadi (Pediatric Infectious Disease)
Human adenovirus (HAdv) infections are very common in children under 5 years of age and can present with varied manifestations including respiratory, gastrointestinal, neurological, cardiac, hematologic, and genitourinary symptoms. We report a 12-year-old boy with HAdv pneumonia who experienced fever remission by the 3rd week of illness. However, he subsequently developed a relapse of fever spikes along with left hypochondriac pain. Upon evaluation, he was found to have splenic infarction (SI). To the best of our knowledge, this is the first case report of adenoviral infection associated with SI.